The value of analytic diversity in urban and sustainability studies. Issue 3 (4th March 2022) - Hess, David J.
ABSTRACT: In a commentary essay, Westman and Castán Broto claim that some choices of analytic strategy are inappropriate for research in urban environmental studies ("Transcending Existing Paradigms: The Quest for Justice in Urban Climate Change Planning." Local Environment, 26(5), 536–541). In contrast, this commentary argues that there can be benefits from research projects that have analytic distinctions between and within sustainability and justice goals in addition to having analytic categories that consider justice and sustainability together. Moreover, projects that focus on one or more sectors with sector-specific research questions, and that focus on goals or frames, can also contribute interesting and novel research in the field. Should such choices of method and analytic strategy be stigmatised or devalued, the research field would lose some of its analytic diversity and robustness. This commentary points to conditions under which such approaches can be beneficial to improved knowledge in both environmental research fields and political fields, and it outlines the types of research questions that can be lost by devaluing such analytic choices.